Tunas Agraria : Implikasi Kewarganegaraan terhadap Hak Kepemilikan Tanah dalam Hukum Agraria Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Latifah Isti’anah; Annada Ashfa Urroozanah; Neysa Kunthi Cahya Latifa (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
This study explores the implications of citizenship on land ownership rights within Indonesian agrarian law. It examines how citizenship status affects the rights to land ownership, focusing on the legal framework established by Indonesian laws, including the Basic Agrarian Law (UUPA) and other relevant regulations. The study employs a qualitative approach, utilizing literature review and case analysis to identify key issues and challenges in the implementation of land ownership laws. Findings reveal that full land ownership rights are exclusively granted to Indonesian citizens, while foreign nationals face significant restrictions. The research highlights several challenges in legal implementation, including bureaucratic inefficiencies and inconsistencies between laws and practical applications. The paper concludes with recommendations for regulatory reforms, improved administrative processes, and enhanced transparency to better support both domestic and foreign stakeholders in land ownership. These recommendations aim to address existing problems and facilitate a more equitable and efficient land management system in Indonesia.